Analisis Perbandingan Hubungan Perdagangan Surat Berharga Syariah Negara dan Variabel Makro Ekonomi Sebelum dan Selama Pandemi Covid-19 - Tunggadewi S, Fortuna; Wulandari, Lia (Diponegoro Journal of Islamic Economics and Business, 2021)
The development of Islamic finance has been very rapid in the last 10 years. From many varoius products, one instrument of Islamic finance that can drives economic growth is sukuk. One type of sukuk issued by Indonesian government is State Sharia Securities (SBSN). this study uses interest rate, exchange rate, and inflation as independent variables. The results of this study reveal that the interest rate variable has no significant impact on SBSN trading through transactions in the secondary market. However, there is a change in interest rate before and after the covid era. Then the exchange rate variable also does not have significant effect on SBSN but it also has an increasing coefficient change after the pandemic happened. Then finally there is inflation that does not have a significant effect on SBSN. However, there is also a change in coefficient which was initially positive to negative after the covid 19 pandemic.